Pengaruh Kepuasan Kerja Terhadap Kinerja Karyawan Printing JuraganBendera.com - Hoiri Hoiri; Iswati Iswati; Emilia Pranata (Manajemen Kreatif Jurnal, 2024)
This research was conducted to find out about "The Effect of Job Satisfaction on Employee Performance" in accordance with the subject matter raised, namely the effect of job satisfaction on employee performance Printing JuraganBendera.com. The background of this research is the importance of employee satisfaction with their work because it can increase or decrease their performance. employees who find their work enjoyable The recipient of the award will be encouraged to improve their abilities, thus having an impact on improving performance. the whole company. This investigation aims to determine the impact of job satisfaction. The purpose of this study was to analyze the effect of job satisfaction on employee performance Printing JuraganBendera.com. The method used in this research is quantitative method. The sample used in this study was the entire number of employees including 30 people using the total sampling method. Technical analysis using simple linear regression with the help of SPSS data processing applications. The conclusion of the results of this study is that job satisfaction significantly and negatively affects the performance of Printing JuraganBendera.com employees.